Serological Evidence of HTLV-I and HTLV-II Coinfections in HIV-1 Positive Patients in Belém, State of Pará, Brazil - VALLINOTO, Antonio Carlos Rosário (2013)
The occurrence of HTLV-I/II and HIV-1 coinfections have been shown to be frequent, probably in consequence of their similar modes of transmission. This paper presents the prevalence of coinfection of HTLV among HIV-1 infected and AIDS patients in Belém, State of Pará, Brazil. A group of 149 patients attending the AIDS Reference Unit of the State Department of Health was tested for the presence of antibodies to HTLV-I/II using an enzyme immunoassay and the positive reactions were confirmed with a Western blot that discriminates between HTLV-I and HTLV-II infections. Four patients (2.7%) were positive to HTLV-I, seven (4.7%) to HTLV-II and one (0.7%) showed an indeterminate pattern of reaction. The present results show for the first time in Belém not only the occurrence of HTLV-II/HIV-1 coinfections but also a higher prevalence of HTLV-II in relation to HTLV-I. Furthermore, it also enlarges the geographical limits of the endemic area for HTLV-II in the Amazon region of Brazil.